General Concept of Regional Development in Geography in Indonesia - Daud Nawir (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the general concept of regional development in geography in Indonesia. This research uses a descriptive qualitative method with a literature study. The result of this research is regional development. In the study of geography, the process of development and development of an area cannot be separated because geography is a science that studies the relationship between humans, ecological space, the area, and the changes that occur, as well as the consequences of the interrelationships between these variables things. The conclusion of this study is that regional development in Indonesia currently still requires well-coordinated spatial planning, planning is defined as determining goals that can be achieved after listening to the inhibiting factors in achieving these goals, selecting and deciding steps for these goals.